Tanggung Jawab Bank Dalam Menjaga Keamanan Dan Kerahasiaan Data Nasabah Perbankan Di Indonesia - Yetno, Alfred (Morality: Jurnal Ilmu Hukum, 2024)
The security of banking customer data has become a focal point within the Indonesian banking industry. In this context, safeguarding the data of customers engaging in banking transactions is crucial to reinforcing customer trust. Data protection is of utmost importance and remains a primary concern in the Indonesian banking sector. Banks are obligated to maintain confidentiality regarding all customer-related data and information, including financial status and personal information. The banking industry must confront the risks of cybercrimes that can jeopardize banking data security, aligning with the current technological advancements. Such data can be exploited for identity theft, fraud, and other criminal activities. Therefore, it is imperative for the banking industry to enhance effective security measures to safeguard customer data from potential breaches. Concerning the aforementioned issues, it is essential to have a clear understanding of the responsibilities of banks in safeguarding banking customer data, along with legal solutions and resolutions related to these issues. The objective of this research is to discuss, analyze, explain, and provide solutions regarding the responsibilities of banks in safeguarding banking customer data in Indonesia. The methodology used in this research is primarily normative legal research, analyzing data and documents derived from legislation, legal principles, legal theories, court decisions, and other relevant sources related to the research topic. Additionally, qualitative methods with a comparative legal approach are employed due to legal vacuums, ambiguities, or contradictions. The research findings indicate that while the Law Number 10 of 1998 concerning Banking provides protection for customer funds, further attention is required for the protection of customer data. Therefore, banks must ensure the security of their electronic systems and take responsibility for customer data. In this regard, prioritizing customer data protection above all is crucial within the Law Number 10 of 1998 concerning Banking to ensure public trust in the banking institution. Strong protection for customer data and efforts to prevent cybercrimes should thus be the primary focus of the banking sector, along with ensuring the readiness of secure electronic systems. Consequently, prioritizing customer protection as consumers is of utmost importance, aligning with the government's commitment and the banking institutions' efforts to maintain public trust in banking services, particularly concerning the security and confidentiality of banking customer data in Indonesia. This principle must be embedded within the Law Number 10 of 1998 concerning Banking concerning the protection of customer data, so that legal cases detrimental to customers due to their errors or force majeure are not solely attributed to customers, but rather, the banking institutions are accountable for the operations of electronic systems, prioritizing customer data protection and making it the top priority in safeguarding customer data in Indonesia.